ANALISIS NILAI-NILAI EDUKATIF DALAM NOVEL TULANG RUSUK MENUJU SURGA KARYA MELLYANA DHIAN (TINJAUAN PSIKOLOGI SASTRA) - Asngadi Rofiq; Khurotul A’yuni (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2021)
Novels as a form of literary work are expected to produce positive values for their readers, so that they can be sensitive to problems related to social life and encourage good behavior. Novels usually tell about the realities of human life with the surrounding environment. The limitations of the problem in this study focused on the analysis of educational values (religious values and moral values) and aspects of literary psychology in the main character in mellyana Dhian's novel Ribs to Heaven. While the purpose of this study is to analyze educational values in Novel Ribs Towards Heaven By Mellyana Dhian Review of Literary Psychology. This research uses Descriptive Qualitative data analysis techniques. Data collection is done by listening method through note-recording technique. Data analysis techniques used are flow analysis that includes three components, namely data reduction, data presentation, and conclusion drawing. From the results of the research shows the conclusion in the novel Ribs Towards Heaven By Mellyana Dhian conveys educational values that are very useful for readers by bringing the story to life, so that it can become more alive and add variety and avoid monotonous things that can make the reader bored. Educational values contained in the novel Ribs Towards Heaven By Mellyana Dhian, based on the results of the analysis consists of two aspects. The educational value is: (a) religious educational value is the highest and absolute spiritual value and is derived from human beliefs or beliefs, in the novel Ribs To Heaven. (b) The moral educational value of the value of dealing with good and bad behavior, in the novel Ribs To Heaven. And a review of literary psychology consisting of three main parts namely id, ego, superego.